Case report: Acute oxalate nephropathy due to traditional medicinal herbs - Wang, Lirui; Zhu, Zhuxian; Li, Jiangtao (Frontiers in Medicine, 2022)
Acute oxalate nephropathy (AON), defined as the association between acute kidney injury (AKI) and the deposition of oxalate crystals in the renal parenchyma, is a rare complication of hyperoxaluria. We report a rare case of AON in an adult due to medicinal herb intake leading to crystal-induced AKI. We recommend that a thorough medication history including the use of medicinal herbs, should be obtained for all patients with a rapid loss of kidney function, especially in the absence of known risk factors for AKI. The use of medicinal herbs with unknown oxalate contents would increase the risk of AON and should be avoided.